A review of the taxonomic diversity, host–parasite interactions, and experimental research on chytrids that parasitize diatoms - Danz, August; Quandt, C. Alisha (Frontiers in Microbiology, 2023)
Diatoms (Bacillariophyta) are a major source of primary production on Earth, generating between 1⁄4 to 1⁄2 of all oxygen. They are found in almost all bodies of water, the ice of mountains, the arctic and the antarctic, and soils. Diatoms are also a major source of food in aquatic systems, a key component of the silica cycle, and are carbon capturers in oceans. Recently, diatoms have been examined as sources of biofuels, food, and other economic boons. Chytrids are members of the Kingdom fungi comprising, at a minimum, Chytridiomycota, Blastocladiomycota, and Neocallimastigales. Most chytrids are saprobes, plant pathogens, or parasites, and play an important role in aquatic ecosystems. Chytrid parasitism of diatoms has been reported to cause epidemics of over 90% fatality, though most of the information regarding these epidemics is limited to interactions between just a few hosts and parasites. Given the ubiquity of diatoms, their importance in natural and economic systems, and the massive impact epidemics can have on populations, the relative lack of knowledge regarding parasitism by chytrids is alarming. Here we present a list of the firsthand accounts of diatoms reported parasitized by chytrids. The list includes 162 named parasitic chytrid-diatom interactions, with 63 unique chytrid taxa from 11 genera, and 74 unique diatom taxa from 28 genera. Prior to this review, no list of all documented diatom-chytrid interactions existed. We also synthesize the currently known methods of infection, defense, and experiments examining diatoms and chytrids, and we document the great need for work examining both a greater breadth of taxonomic diversity of parasites and hosts, and a greater depth of experiments probing their interactions. This resource is intended to serve as a building block for future researchers studying diatom-parasite interactions and global planktonic communities in both fresh and marine systems.